In vitro Anti-Inflammatory Activity of Common Lantana (Lantana camara) Leaf and Flower Extract Topical Ointments: Comparative Analysis and Sensory Profile - Robosa, Jeorge Conrad Abulag; Ban, Queen Loraine Delgado; Cabigon, Kiziah Odchigue; Saldo, Ian Jay Paspe (Asian Journal of Biological and Life Sciences, 2025)
Background: Lantana camara (Common Lantana) is an invasive species reported to possess anti-inflammatory properties. Objectives: This study evaluated in vitro anti-inflammatory activity of leaf and flower extracts formulated into topical ointments and assessed sensory profiles. Materials and Methods: Extracts were prepared and tested using Egg Albumin Denaturation Assay at concentrations up to 2000 ppm; diclofenac served as standard. Sensory evaluation covered fragrance, texture, and appearance. Results: Diclofenac showed highest inhibition (15.14% at 2000 ppm) while leaf extract and flower extract showed 5.42% and 4.52% respectively; sensory mean acceptability for leaf and flower ointments were 3.15 (SD=0.85) and 3.08 (SD=0.88). Conclusion: L. camara extracts show modest in vitro anti-inflammatory activity and acceptable sensory attributes; further optimization of extraction and formulation is suggested.
Keywords: Anti-inflammatory; Lantana camara; Ointment; Sensory profile